The Effects of External Focus of Attention on Shoulder Muscle Activities during Forehand Drive in Table Tennis - Mohammad Reza Hatami; Keyvan Sharifmoradi; Mahdi Majlesi (Biyumikānīk-i varzishī)
Objective: The aim of this study was to evaluate the impact of the external focus of attention on the rotator cuff muscle activity for the timely hit forehand drive by table tennis players.